A Case of Synchronous Malignancy with Novel Missense Mutation in a Child: Is This Li-Fraumeni Syndrome or a Novel Case Masquerading as Li-Fraumeni Syndrome?? - Raj, Vinod; Redkar, Rajeev; Tewari, Shruti; Bangar, Anant; Kanakia, Swati (Indian Journal of Medical and Paediatric Oncology, 2020)
We report the case of an 11-month-old child who presented with a change in voice, increased weight, and hirsutism, who was also found to have elevated levels of serum cortisol and testosterone, showing three synchronous malignancies in the liver, left adrenal gland, and posterior mediastinum. Clinical exome sequencing report revealed germline TP53 (P177A) and MLH3 (V741P) mutations with NMYC positive neuroblastoma. At the outset, this may look like a Li-Fraumeni syndrome (LFS) with TP53 germline mutation but lacks other features to be termed as LFS or Li-Fraumeni-like syndrome. The gene mutation variant found in this case (P177A) is a novel missense mutation which has never been reported, and the MLH3 gene mutation variant V741P has not been previously associated with any of the malignancies seen in this child.
Keywords: Adrenocortical malignancy; hepatoblastoma; mismatch repair gene; neuroblastoma; synchronous malignancy